C17 Track TGHD Minipig – Startbox back and Forth Test. (17th September 2014) - Wirsig, M; Schuldenzucker, V; Schramke, S; Frank, F; Schubert, R; Ott, S; Marcegaglia, M; Hölzner, E; Reilmann, R
Abstract : Background: This study aims to investigate characteristics of the tgHD Libéchov minipig as a model for HD. So far no cognitive and behavioural assessments are established for minipigs. The "startbox back and forth test" introduced here is part of the cognitive-behavioural battery under development. Aim: The aim of this study is to assess the feasibility and tolerability of applying the "startbox back and forth test" in minipigs and explore its sensitivity to detect cross-sectional and longitudinal differences between tgHD and wt minipigs. Material and methods: Fourteen tgHD (124 Q) and eighteen wt Libéchov-minipigs were included. The setup the pigs are trained and tested in consists of a walkway and two startboxes (SB 1 and SB 2) on both ends, connected through trapdoors. In the training phase, minipigs are trained to run back and forth between SB 1 and SB 2 and are rewarded when reaching the opposite startbox. During the testing phase the pigs are not rewarded, while the option to run back and forth is maintained. The learning target in this test is not to run back and forth, because of the missing reward. During training and testing, completed runs within 5 min are counted. The test is stopped when a pig stays 1.5 min either in a startbox or in the walkway (assuming that it has learnt there is no reward to expect). Biannually, each pig completes two training sessions and subsequently the testing session is performed. Results: All data has been successfully acquired in all tgHD and wt minipigs suggesting good tolerance of the method. An ANOVA analysis comparing the differences in behaviour between tgHD and wt minipigs is in progress. Conclusion: The data collected to date demonstrates that application of the "startbox back and forth test" is feasible and well tolerated. It is hypothesised that recognition of the lack of being awarded is impaired in tgHD minipigs compared to controls. This is currently assessed and we expect to report first results at the meeting.